Bilateral cataract surgery improves neurologic brake reaction time and stopping distance in elderly drivers. Issue 7 (2nd June 2021) - Nowosielski, Yvonne; Leitner, Benedikt; Rauchegger, Teresa; Angermann, Reinhard; Psomiadi, Angeliki; Palme, Christoph; Laimer, Johannes; Liebensteiner, Michael; Zehetner, Claus
Abstract: Aims: To determine brake reaction times before and after bilateral cataract surgery in elderly drivers. Methods: Sixty‐four patients were evaluated on the day of and 4 weeks after bilateral cataract surgery. Forty‐three healthy individuals with a valid driving licence served as the control group. A driving simulator was used to determine brake reaction times after receiving a visual stimulus. Total brake reaction time (BRT) as well as neurologic reaction time (NRT), foot transfer time (FTT) and brake pedal travel time (BPTT) were measured, and the measurements obtained before and after cataract surgery were compared. The correlations between NRT, best‐corrected visual acuity (BCVA) and contrast sensitivity (CS) were assessed. Results: Out of the 64 patients with bilateral cataract, 53 were assessed for postsurgical measurements. All time measures improved significantly after cataract surgery (BRT, 815.7(224) versus 647.9(148) ms; NRT, 364.7(91) versus 283.5(44) ms; FTT, 290.8(62) versus 248.6(58) ms; and BPTT, 160.6(96) versus 116.6(72) ms, p < 0.001). The calculated stopping distance improved significantly after surgery (22.3(6) versus 19.9(4) m at 50 km/h). Best‐corrected visual acuity (BCVA) and contrast sensitivity (CS) improved significantly after surgery (0.25(0.2) versus 0.05(0.05), n  = 53, p < 0.001; 1.4(0.2) versus 1.6(0.1), p < 0.001, respectively). There was a significant negative correlation between CS and NRT before surgery ( r  = −0.253, n  = 64, p = 0.04, Pearson's correlation). Conclusion: Our findings show a significant effect of CS on neurological BRTs and the corresponding stopping distances. This highlights the importance of presurgical CS evaluation as a critical factor in cataract surgery decisions in elderly drivers.